PENINGKATAN PERKULIAHAN BAHASA INDONESIA UNTUK MEMBINA KETERAMPILAN MAHASISWA Abstract DALAM MENULIS KARYA ILMIAH - Zarnzani, Zarnzani; Syamsi, Kastam; Santoso, Joko; Hartono, Hartono (Jurnal Cakrawala Pendidikan, 2016)
icle is based on a classroom action research aimed at 1I11"’1r"l11 ....n’TO’fl 01n’t in classes of Bahasa Indonesia at ........... ,..,., ............, .... V ..... IIoJI’lIlo"_IJI,.V were VIJI,._ "’_.II.Jl.II.V Language A....Iu.’ """’Q".4."AVJLA’" A....Iu.· """’’’’’... ’’.a.V’A.a. Study Programs, numbering fifty-one, and thirty-eight, respectively. The analysis the __.11.’&"’1-’.11..11. __ through observations, tests, and writing assignments, was and qualitatively descriptive. o"’r.ln........\ 111C"n1!4r’Ø’t’ . were based on the level works, which was indicated by the scores obtained. The results of the action research can be as follows. First, the students’ skills writing scientific works are categorized good so that the learning model employed in the research, composed of discussion, assignment the form writing practice, and lecture related to theory of writing complete with written material of various forms, is considered good or appropriate. Second, an exploration of students’ needs and a discussion to an agreement about the learning material, model, and evaluation have improved their awareness of significant matters and their responsibilities in classes.